2019
DOI: 10.1007/s11012-019-01103-2
|View full text |Cite
|
Sign up to set email alerts
|

Water transport and absorption in pharmaceutical tablets – a numerical study

Abstract: The quality of a coated pharmaceutical tablet can be strongly affected by the interactions of water droplets with the porous substrate during processes such as coating process. Three different mechanisms co-exist in the coating process: water spreading, absorption and evaporation. Disentangling the fundamental understanding of these phenomena can therefore be crucial for achieving a higher quality of the products (e.g. a longer shelf-life of the tablets) and for controlling the efficiency of the process. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…We anticipate similar but possibly more complex invasion patterns in three-dimensional anisotropic materials. Having in mind that transverse invasion would then take place on a two-dimensional plane, we can expect an even slower invasion dynamics along such a direction [32]. Future simulations should investigate the impact of threedimensional invasion dynamics on the extent of the asymmetric functioning range currently observed.…”
Section: Discussionmentioning
confidence: 98%
“…We anticipate similar but possibly more complex invasion patterns in three-dimensional anisotropic materials. Having in mind that transverse invasion would then take place on a two-dimensional plane, we can expect an even slower invasion dynamics along such a direction [32]. Future simulations should investigate the impact of threedimensional invasion dynamics on the extent of the asymmetric functioning range currently observed.…”
Section: Discussionmentioning
confidence: 98%
“…The particles in contact with the fluid starts to dissolve. At the same time the fluid enters the tablet through the pores and its network resulting in the disintegration of the tablet into smaller pieces and this stage is effectively controlled by the concentration of pores [ 242 , 243 , 244 , 245 , 246 , 293 , 345 , 346 , 347 ]. By extracting the information of the pore network and its permeability from a SEM image, Zhang et al [ 348 ] has shown that one can estimate the drug release rate by computational fluid dynamic simulation.…”
Section: Tablet Characterizationmentioning
confidence: 99%
“…To further explore the evolution of droplet The power-law dependency of the penetration mass is in line with the previous findings for a droplet impacting a porous medium. 52,53 In the following, we will propose a new model to describe the evolution of droplet penetration mass. As the analysis of Fig.…”
Section: Articlementioning
confidence: 99%